EPISTIMOLOGI KURIKULUM BAHASA ARAB DI SEKOLAH MENENGAH MUTAWASITAH PIRAYA NAWIN KLONGHIN WITTAYA PATANI THAILAND SELATAN - Nurcholis, Ahmad; Salaeh, Basmah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
This article aimed to discuss the discourse of learning Arabic, the nature and its benefits that has been obtained from a real phenomenological qualitative research at Piraya Nawin School in Wittaya Thailand. The epistemology of Arabic language curriculum development in Thailand focus on the use of Arabic as a media for both oral and written communication. This curriculum development aims to understand Qur'an, Hadith, and many other religion books written in Arabic. The curriculum development in this school was appropriate with the vision and mission, to build the the good character through Arabic habituation in the school environment. The operational standard for implementing the Arabic curriculum development was determined by the school itself, without any government intervention. For example, memorizing Arabic mufradat. There were some obstacles such as the students who were not interested in memorizing mufradat and less of discipline to go to school. Arabic still does not become an important thing for students as well as its probelmatics that pay little attention to the different aspects of student competence.